Liquidity And Performance Of Banks Listed On The Ghana Stock Exchange - Magnus Kofi Quansah; Oscar Agyemang Opoku (Pusat Publikasi Nusantara, 2023)
The aim of the study was to examine the effect of liquidity on the performance of banks listed on the Ghana Stock Exchange. The study employed annual panel data of 8 out of the 9 banks listed on the Ghana Stock Exchange. The random effect model was used with the aid of Hausman test. The data used for the study spans from 2015 to 2019. The study found among other things that 34.8% variation in the return on asset of banks listed on the Ghana Stock Exchange can be explained by sales growth rate, firm size and liquidity. The study revealed that liquidity and sales growth do not have any statistically significant effect on the profitability of banks listed on the Ghana Stock Exchange. However, the size of a bank in terms of its total assets has a significant effect on the profitability of banks listed on the Ghana Stock Exchange. The study finds that liquidity and sales growth do not have any statistically significant effect on the profitability of banks listed on the Ghana Stock Exchange, the size of a bank has statistically significant effect on the return on assets of banks listed on the Ghana Stock Exchange. It was recommended that banks listed on the GSE must work on reducing their interest expense to enhance their liquidity positions. Managers of banks listed on the GSE must work at increasing their asset base as there exists a significant relationship between size and profitability